The Relationship Between Nutritional Status and Some Socio-Economic Factors in Primary School Children in Shiraz, Iran - Saeedeh Masjedi; Mohammad Hassan Eftekhari; Siavash Babajafari; Hamid Reza Tabatabaee (Shiraz University of Medical Sciences, 2016)
Background: The worldwide prevalence of malnutrition which is the root cause of many health problems, and presented as underweight and overweight, has increased in past decades. Therefore efforts are required to prevent malnutrition and its associated complications. Objectives: The present study aimed to assess the relationship between nutritional status and some socio-economic factors in elementary school children in Shiraz, Iran. Materials and Methods: This cross-sectional study was performed on 740 primary school students in Shiraz selected through cluster random sampling. The data consisted of personal characteristics, including demographic features, education grade, height, weight, birth order, number of children in the family, parents' age, parents' education levels, parents' occupation, immigration history, divorce, birth weight, breastfeeding period, birth season, history of obesity in the first degree relative, sleep duration, time spent on watching TV, using computer, and playing video games, eating meal and pre-meal patterns, and economic status. Besides, the students' Body Mass Indices (BMI, weight (kg)/height × height (m 2)) were measured in order to determine student's percentiles. Results: The study results revealed that 73 (9.9%), 524 (70.8%), 101 (13.6%), and 42 (5.7%) students were underweight, normal, overweight, and obese, respectively. Among the evaluated factors, only mid-afternoon meal was significantly related to nutritional status. In comparison to having more than two pre-meals a day, not consuming afternoon pre-meal increased the chance of being underweight by about 10.1 folds. Moreover, the chance of being underweight increased in children who did not consume afternoon pre-meal due to less energy intake. Conclusions: This study revealed a high prevalence of malnutrition among the primary school students. Yet, further studies are required to accurately identify the effective factors for prevention and treatment of malnutrition in school age children.